The completed hickory dickory dock - Aylesworth, Jim.; Christelow, Eileen (New York : Atheneum, 1990)
Completes the classic nursery rhyme about the mouse that ran up the clock.
1.9
K-3
Keywords: Nursery rhymes, American; Children's poetry, American; Nursery rhymes; American poetry; Nursery rhymes